A COMPARATIVE STUDY OF EEL (ANGUILLA ANGUILLA (L.)) POPULATION STRUCTURE IN THREE SITES IN ITALY, AND PRELIMINARY CONSIDERATIONS ON THE RELATIVE CONTRIBUTION TO ESCAPEMENT. - CICCOTTI, ELEONORA; CAPOCCIONI, F; CAPRIOLI, R; DE LEO, G. (country:BE, 2008)
Eel population structure has been evaluated in three sites, (river Tiber, Caprolace and Lesina lagoons) in Italy, within a project aimed at the setting up of a integrated approach to the eel conservation and management in the Mediterranean area. First results show both differences and similarities between the three sites: all populations consist mostly of yellow eels, but the Tiber population consists mostly of small sizes and young specimen, whereas Caprolace and L esina populations show a comparable size distribution class with a predominance of larger individuals, even if age structure in the two lagoons is different. Furthermore, the Tiber population shows a sex ratio with the undifferentiated fraction larger than the mature and the latter consists mostly of males, while in both lagoons a predominance of females has been observed. Evident differences have been observed in infection rate by Anguillicola crassus: very high in the Tiber and intermediate in Lesina, while no infestation has been detected in eels from Caprolace. These results allow to make some preliminary considerations on the different contribution of the riverine and lagoon environments to the escapement of silver eels, not only from a quantitative but also qualitative point of view.